Peranan Sektor Tembakau dan Industri Rokok dalam Perekonomian Indonesia: Analisis Tabel I-O Tahun 2000 - Prajogo Utomo Hadi; Supena Friyatno (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2008)
EnglishDuring the last decade, the increasing intensity of anti-tobacco campaign underpinned by health consideration that has been reinforced by the ratified Framework Convention on Tobacco Control (FCTC), the reduced government support to tobacco production, and the increasing community’s awareness on the importance of healthy life, has been threatening the world and the Indonesian tobacco economy. The world tobacco economy is expected to be slowing down and severely affects the Indonesia’s tobacco economy. In this connection, this paper is aimed at analyzing the current situation and the roles of tobacco and cigarette industry sectors in the Indonesian economy. Important results of the analysis are as follows: (i) the tobacco production during the 2000-2006 period was decreased by 5.98% per annum; (ii) the per capita cigarette consumption tended to increase with the increased per capita income; (iii) the tobacco and the cigarette sectors shared about 7% of the government domestic revenues, but more depleting rather than generating foreign exchanges; (iv) the tobacco and cigarette industry sectors have small share in the creation of output value, value added and employment, but have relatively high output multiplier, particularly the tobacco sector; and (v) the tobacco sector was able to pull its upstream sectors and push its downstream sectors to develop, while the cigarette sector was able only to push its downstream sector. It is suggested, therefore, that: (i) the future development of tobacco and cigarette sectors needs to consider the balance between economic and health aspects; and (ii) the nicotine and tar contained in the cigarettes needs to be reduced while exploring alternative economically feasible of non-cigarette uses of tobacco.IndonesianSelama dasawarsa terakhir, meluasnya kampanye anti tembakau karena pertimbangan kesehatan yang diperkuat dengan telah diratifikasinya Konvensi Kerangka Pengendalian Tembakau, berkurangnya dukungan pemerintah untuk pengembangan ekonomi tembakau serta meningkatnya kesadaran masyarakat akan pentingnya hidup sehat, maka ancaman terhadap ekonomi tembakau dunia dan Indonesia mulai terasa. Dikhawatirkan ekonomi tembakau dunia akan terus melesu dan berdampak pada Indonesia. Sehubungan dengan itu, makalah ini bertujuan untuk menganalisis kinerja serta peranan sektor tembakau dan sektor industri rokok dalam perekonomian nasional Indonesia. Beberapa temuan penting adalah sebagai berikut (i) produksi tembakau selama periode 2000-2006 menurun rata-rata 5,98 persen per tahun, (ii) konsumsi rokok per kapita cenderung naik dengan naiknya pendapatan per kapita, (iii) sektor tembakau dan sektor industri rokok memberikan sumbangan sekitar 7 persen terhadap penerimaan negara dari dalam negeri, namun lebih banyak menguras daripada menghasilkan devisa negara, (iv) peranan sektor tembakau dan sektor industri rokok dalam penciptaan nilai output, nilai tambah, dan penyerapan tenaga kerja kurang signifikan, namun keduanya mempunyai angka pengganda output cukup besar, terutama sektor tembakau, dan (v) sektor tembakau mampu menarik sektor hulunya dan mendorong sektor hilirnya untuk berkembang, sedangkan sektor industri rokok hanya mampu mendorng sektor hilirnya. Disarankan agar (i) dalam pengembangan sektor tembakau dan sektor industri rokok ke depan perlu mempertimbangkan keseimbangan antara aspek ekonomi dan aspek kesehatan dan (ii) kandungan nikotin dan tar dalam rokok perlu dikurangi serta mencari alternatif penggunaan tembakau untuk nonrokok yang fisibel secara ekonomi.